Um método para produção de videoaulas no contexto educacional - Silva, Luiza Raquel Souza e (2018)
The video classes are used as a pedagogical resource in distance learning and many individuals, even without being linked to an educational institution, resort to them as a source of research and study material on digital media platforms. Because this is an important teaching resource, it is important to develop procedures that improve the content production through audiovisual technology, developing techniques that assist the production of instructional materials. However, the production of video classes by interdisciplinary teams is often performed without proper standardization, which does not guarantee a product that meets the pedagogical and technical standards. Faced with this challenge, we question: is it possible to establish steps for the process of making video classes in order to organize their production? This is the starting point for this research, which aims to propose a method for systematizing the production of video classes in order to optimize this educational technology. For that, a literature review was carried out, allowing to identify the concepts of Learning Theory and Instructional Design, as well as works related to the theme. Based on the data collected, this research proposes a method for the production of video classes, with the instrument of routing and a instrument of evaluation of production, in order to guide the production teams throughout the process and to allow the analysis of the material produced. The method and the instruments are experimented with in the pre-production, production and post-production stages of videoclasses, so as to permit the analysis of their viability.